Food-Related Parenting Practices and Adolescent Weight Status: A Population-Based Study - Loth, Katie A. (American Academy of Pediatrics, 2013)
OBJECTIVE: To examine food-related parenting practices (pressure-to-eat and food restriction) among mothers and fathers of adolescents and associations with adolescent weight status within a large population-based sample of racially/ethnically and socioeconomically diverse parent-adolescent pairs. METHODS: Adolescents (N = 2231; 14.4 years old [SD = 2.0]) and their parents (N = 3431) participated in 2 coordinated population-based studies designed to examine factors associated with weight status and weight-related behaviors in adolescents. Adolescents completed anthropometric measurements and surveys at school. Parents (or other caregivers) completed questionnaires via mail or phone. RESULTS: Findings suggest that the use of controlling food-related parenting practices, including pressure-to-eat and restriction, is common among parents of adolescents. Mean restriction levels were significantly higher among parents of overweight and obese adolescents compared with nonoverweight adolescents. However, levels of pressure-to-eat were significantly higher among nonoverweight adolescents. Results indicate that fathers are more likely than mothers to engage in pressure-to-eat behaviors and boys are more likely than girls to be on the receiving end of parental pressure-to-eat. Parental report of restriction did not differ significantly by parent or adolescent gender. No significant interactions by race/ethnicity or socioeconomic status were seen in the relationship between restriction or pressure-to-eat and adolescent weight status. CONCLUSIONS: Given that there is accumulating evidence for the detrimental effects of controlling feeding practices on children’s ability to self-regulate energy intake, these findings suggest that parents should be educated and empowered through anticipatory guidance to encourage moderation rather than overconsumption and emphasize healthful food choices rather than restrictive eating patterns.